Frequent Dilatation of the Descending Aorta in Children With Hypoplastic Left Heart Syndrome Relates to Decreased Aortic Arch Elasticity. Issue 10 (October 2015) - Voges, Inga; Jerosch‐Herold, Michael; Wegner, Philip; Hart, Christopher; Gabbert, Dominik; Al Bulushi, Abdullah; Fischer, Gunther; Andrade, Ana Cristina; Pham, Hoang Minh; Kristo, Ines; Kramer, Hans‐Heiner; Rickers, Carsten
Abstract : Background: Patients with hypoplastic left heart syndrome after a Norwood operation show dilatation and reduced distensibility of the reconstructed proximal aorta. Cardiac magnetic resonance imaging (CMR) and angiographic examinations indicate that the native descending aorta (DAo) is also dilated, but this has not been studied in detail. Methods and Results: Seventy‐nine children with hypoplastic left heart syndrome in Fontan circulation (aged 6.3±3.2 years) and 18 control participants (aged 6.8±2.4 years) underwent 3.0‐tesla CMR. Gradient‐echo cine and phase‐contrast imaging was applied to measure cross‐sectional areas (CSAs), distensibility, pulse wave velocity, and the incremental elastic modulus of the thoracic aorta. CSA of the DAo in patients was also compared with published percentiles for aortic CSA. Patients had significantly larger CSA of the DAo at the level of pulmonary artery bifurcation (229.1±97.2 versus 175.7±24.3 mm/m 2, P =0.04) and the diaphragm (196.2±66.0 versus 142.6±16.7 mm/m 2, P <0.01). In 41 patients (52%), CSA of the DAo was >95th percentile level for control participants, and the incremental elastic modulus of the aortic arch and the DAo was higher than in patients with normal CSAs (arch: 90.1±64.3 versus 45.6±38.9 m/s; DAo: 86.3±53.7 versus 47.1±47.6 m/s; P <0.01). Incremental elastic modulus of the aortic arch and the DAo correlated with the CSA of the DAo (arch: r =0.5; DAo: r =0.49; P <0.01). Conclusions: Children with hypoplastic left heart syndrome frequently show dilatation of their DAo associated with increased stiffness of the aortic arch. Higher aortic impedance increases the afterload of the systemic circulation and likely contributes to the burden of the systemic right ventricle.